2007
DOI: 10.1002/chem.200601112
|View full text |Cite
|
Sign up to set email alerts
|

Well‐Defined Cationic Alkyl– and Alkoxide–Aluminum Complexes and Their Reactivity with ε‐Caprolactone and Lactides

Abstract: We describe the synthesis, structure, and reactivity of low-coordinate Al-alkyl and -alkoxide cationic complexes incorporating the sterically bulky aminophenolate bidentate ligand 6-(CH(2)NMe(2))-2-CPh(3)-4-Me-C(6)H(2)O- (N,O). These complexes are derived from the ionization of neutral dialkyl Al complexes (N,O)Al2) (1 a, R=Me; 1 b, R=iBu), readily obtained by alkane elimination between AlR3 and the corresponding aminophenol ligand, with the alkyl abstracting reagents B(C(6)F(5))3 and [Ph(3)C][B(C(6)F(5))4]. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 62 publications
4
77
1
2
Order By: Relevance
“…A number of four‐, five‐ and six‐coordinate cationic aluminum species are known with their applications ranging from polymerization of cyclic ethers (propylene oxide), esters (ϵ‐capralactone), isobutene, and β‐hydrogen‐transfer reactions to olefins or ketones . It is not surprising that two and three‐coordinate cationic aluminum species, due to the coordinative unsaturation at the metal, are very rare, and the well‐characterized ones are shown in Figure …”
Section: Figurementioning
confidence: 99%
“…A number of four‐, five‐ and six‐coordinate cationic aluminum species are known with their applications ranging from polymerization of cyclic ethers (propylene oxide), esters (ϵ‐capralactone), isobutene, and β‐hydrogen‐transfer reactions to olefins or ketones . It is not surprising that two and three‐coordinate cationic aluminum species, due to the coordinative unsaturation at the metal, are very rare, and the well‐characterized ones are shown in Figure …”
Section: Figurementioning
confidence: 99%
“…For ligands containing both oxygen and nitrogen as potential bridging atoms, it is found that compounds having oxygen bridges between aluminium atoms [23,24,39,[47][48][49][50] predominate over those with nitrogen bridges. [37,51] Examples are known with both O and N atoms bridging in hydroxypyridine ligands (in an isolobal disposition to carboxylatebridged ligands) [25] or with an amidate group [52][53][54][55] between two aluminium atoms.…”
Section: Resultsmentioning
confidence: 98%
“…The values observed in 5 are in the range observed for other complexes with a bridging N atom [37,57,58] and comparable to Al-N dative bond lengths. [50,59] The six-membered ring chelate Al metallacycle is significantly twisted, angles between the planes containing the Al 2 N 2 and C 6 H 2 rings ranging from 32.88°to 33.48°. [32,38] In view of these experimental results, we were interested in understanding the factors that determine the tendency to stabilize mononuclear or dinuclear structural dispositions in (amido)(hydrido)(phenoxido) aluminium compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Die Reaktionsprodukte sind C 6 D 5 CH 3 und (Et 3 Si) 2 O. Zwischenzeitlich wurde Methanol gebildet, das aber weiterreagierte. [25] Zum Vergleich haben wir auch die katalytische Aktivität von AlBr 3 in der CO 2 [26] und wurden unter anderem für die Herstellung von Aluminiumoxiden bei hçheren Temperaturen eingesetzt. [22] In vielen der obigen Reaktionen, insbesondere denen mit langen Reaktionszeiten und unter Erhitzen, war Et 4 Si das Endprodukt und nicht das erwartete Siloxan (Et 3 Si) 2 O. Da es bekannt ist, dass Siloxane und Silylether unter Substituentenaustausch in Gegenwart einer Lewis-Säure reagieren, [23] wurde (Et 3 Si) 2 Es sollte auch nicht unerwähnt bleiben, dass CO 2 nicht mit 1 reagierte, auch nicht nach 30 h bei 80 8C.…”
Section: Angewandte Chemieunclassified